2017
DOI: 10.20524/aog.2017.0135
|View full text |Cite
|
Sign up to set email alerts
|

Long-term change in incidence and risk factors of cirrhosis and hepatocellular carcinoma in Crete, Greece: a 25-year study

Abstract: BackgroundNo sequential long-term data exist for Greece on the etiological evolution and incidence of cirrhosis and hepatocellular carcinoma. Therefore, we studied their etiological evolution over a period of 25 years in the island of Crete.MethodsWe studied 812 cases of cirrhosis (561 male, median age 69 years) and 321 cases of hepatocellular carcinoma (234 male, median age 70 years) from the database of our Center. Cases were classified into five-year periods according to incidence and etiology (hepatitis B,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…It is estimated that 18 to 33% of the total number of HCCs is caused by past and present alcohol intake in several European countries [ 29 ]. Recently, Karageorgos and colleagues showed a change in incidence and risk factors for cirrhosis and HCC in Crete, with significantly decreased HCV association and alcohol as the top-ranked risk factor [ 30 ]. In a German cohort of 458 HCC patients, chronic alcohol abuse was identified as the leading risk factor in 57.2% [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that 18 to 33% of the total number of HCCs is caused by past and present alcohol intake in several European countries [ 29 ]. Recently, Karageorgos and colleagues showed a change in incidence and risk factors for cirrhosis and HCC in Crete, with significantly decreased HCV association and alcohol as the top-ranked risk factor [ 30 ]. In a German cohort of 458 HCC patients, chronic alcohol abuse was identified as the leading risk factor in 57.2% [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of cirrhosis was confirmed by liver biopsy in compensated cirrhosis and clinical evidence in decompensated cirrhosis. They found that NAFLD cirrhosis constituted 15.5% of all cases of cirrhosis [ 17 ]. Hsiang et al reported a retrospective study from a secondary care hospital in South Auckland (New Zealand).…”
Section: Epidemiologymentioning
confidence: 99%
“…HCC is characterized by a poor prognosis and high aggressivity and is difficult to diagnose early (3). It is widely known that nonalcoholic fatty liver disease, hepatitis C virus, and alcohol abuse are strongly related to the occurrence of HCC (4)(5)(6). Liver biopsy is the most reliable method for diagnosing HCC; however, due to its invasiveness, this method is not suitable for large-scale liver cancer screening (7).…”
Section: Introductionmentioning
confidence: 99%